Berberine-Loaded Thiolated Pluronic F127 Polymeric Micelles for Improving Skin Permeation and Retention - Niu, Jiangxiu (Int J Nanomedicine, 2020)
BACKGROUND: Challenges associated with local antibacterial and anti-inflammatory drugs include low penetration and retention of drugs at the expected action site. Additionally, improving these challenges allows for the prevention of side effects that are caused by drug absorption into the systemic circulation and helps to safely treat local skin diseases. METHODS: In the current study, we successfully prepared a thiolated pluronic F127 polymer micelles (BTFM), which binds to keratin through a disulphide bond, to produce skin retention. In addition, the small particle size of polymer micelles promotes the penetration of carriers into the skin. The current study was divided into two experiments: an in vitro experiment; an in vivo experiment that involved the penetration of the micelle-loaded drugs into the skin of rats, the skin irritation test and the anti-inflammatory activity of the drug-loaded micelles on dimethyl benzene-induced ear edema in mice. RESULTS: Results from our in vitro transdermal experiment revealed that the amount of drug absorbed through the skin was decreased after the drug was loaded in the BTFM. Further, results from the vivo study, which used fluorescence microscopy to identify the location of the BTFM after penetration, revealed that there was strong fluorescence in the epidermis layer, but there was no strong fluorescence in the deep skin layer. In addition, the BTFM had a very good safety profile with no potentially hazardous skin irritation and transdermal administration of BTFM could significantly suppress ear edema induced by dimethyl benzene. Therefore, these findings indicated that BTFM reduced the amount of drug that entered the systemic circulation. Our results also demonstrated that the BTFM had a certain affinity for keratin. CONCLUSION: Our experimental results suggest that the BTFM may be an effective drug carrier for local skin therapy with good safety profile.